Juridical Analysis of Human Trafficking Crimes Based on a Case Study at the District Court of Kotabumi - Apriyanto, Apriyanto; Haryadi, Slamet (CV. Ulil Albab Corp, 2025)
This study discusses the crucial role of the Class II Correctional Center (BAPAS) in Kotabumi in addressing diversion cases for juveniles in conflict with the law. BAPAS serves as an institution that provides guidance and support to these children, aiming to avoid negative stigma and restore social relationships among the child, family, and community. The diversion process involves various stakeholders, including police, prosecutors, judges, and community advisors, who actively assist the child throughout the legal proceedings. However, this research also identifies challenges faced by BAPAS, both internally and externally. Internal challenges include insufficient financial support, limited facilities, and an inadequate number of community advisors. Meanwhile, external challenges encompass the community's limited understanding of the diversion process and the dominance of police in the proceedings, which often leads to failures in achieving diversion agreements. Recommendations for enhancing the effectiveness of BAPAS include improving training for community advisors, providing adequate facilities, and increasing operational budgets from relevant institutions. This study emphasizes the importance of collaboration among government, society, and legal institutions to create an environment that supports the reintegration of children into society and promotes restorative justice.